Modern Painters: Dickens and Cézanne - Jeremy TAMBLING (E-REA)
The article compares the ways of looking in Dickens’ novels and in Cézanne’s art, drawing on the work of Merleau-Ponty for commentary on Cézanne, and on the commentaries on Merleau-Ponty by Lacan. It investigates the way in which Dickens, not often considered as having a visual interest, is modern in modes of perception, and tries to illuminate Merleau-Ponty’s sense of embodiment, as seen in Cézanne, through illustrations and examples drawn from Dickens.